OPTIMAL PORTFOLIO CONSTRUCTION MAXIMIZING INVESTOR UTILITY: A STUDY OF BBRI AND WIKA STOCKS - Nur Afifah Az-Zahra; Muhammad Zaqi Amali; Arief Surya Lesmana; Dadan Darmawan Muttaqien (Universitas Kuningan, 2026)
This study examines optimal portfolio construction within the context of the Indonesian capital market, focusing on an investor utility approach—specifically regarding BBRI and WIKA stocks. In an investment environment characterized by the risk-return trade-off, a utility-based approach is essential for explicitly capturing investor risk preferences. Consequently, this study aims to determine the optimal portfolio composition that maximizes investor utility, accounting for a specific level of risk aversion. The study employs a mean-variance theoretical framework extended by a quadratic utility function, with investor preferences represented by a risk aversion coefficient of 2.5. Stock return data are used to calculate expected returns and portfolio risk, as well as to determine optimal weights through a utility optimization process. The analysis reveals that the optimal portfolio is dominated by BBRI stock, comprising 98.28% of the portfolio, while WIKA stock accounts for only 1.72%. This combination yields an expected return of 0.43% and a risk level of 7.81%. The maximum utility value obtained is -0.0034. Although this utility value is negative, it remains theoretically valid; the utility function used is relative in nature and heavily influenced by the magnitude of risk and the investor's level of risk aversion during the optimization process. These findings indicate that, under certain conditions, a portfolio dominated by low-risk assets is preferred by investors with high risk aversion, even if it results in an absolute negative utility value. Thus, the study underscores the importance of considering investor risk preferences in investment decision-making and demonstrates that a utility value need not be positive to reflect an optimal investment decision.